Forage supply in thinned Caatinga enriched with buffel grass (Cenchrus ciliaris L.) grazed by goats and sheep - doi: 10.4025/actascianimsci.v34i2.12548 - Formiga, Luiza Daiana Araújo da Silva; Pereira Filho, José Morais; Silva, Aderbal Marcos de Azevêdo; Oliveira, Nadjanara Souza; Soares, Diogo da Costa; Bakke, Olaf Andreas (Acta Scientiarum. Animal Sciences, 2011)
Forage supply from herbs was assessed in a thinned Caatinga enriched with buffel grass (Cenchrus ciliaris L.) exposed to goat and sheep grazing. The 2.4 ha experimental area, located at the Experimental Station of the Federal University of Campina Grande, in Santa Terezinha, Paraíba State, Brazil, was divided into four 0.6 ha paddocks, which were further subdivided into two 0.3 ha experimental plots. Twelve F1 (Boer x SRD) goats and 12 Santa Inês sheep were divided in four groups of six animals of the same species. The herbaceous vegetation was separated into buffel grass (Cenchrus ciliaris L.), dicotyledons and other grass species. Treatments were randomized to plots according to a completely random design with two treatments, four replications, with measures repeated in time (July/1, Aug/1, Sept/1 and Oct/1. Buffel grass dry mater (DM) availability was higher in the sheep grazed than in the goat-grazed area. Buffel grass DM supply did not change from July to September, while dicotyledons DM supply decreased. Grazing affected availability, accumulation rate and supply of the forage produced (DM basis) by dicotyledonous herbs. Buffel grass forage availability was not affected during the experimental period.